Antipyretic and anti-nociceptive effects of methanol extract of leaves of Fimbristylis miliacea in mice model. (28th October 2019) - Roy, Roni; Ud Daula, A.F.M Shahid; Akter, Afroza; Sultana, Sharmin; Barek, Md Abdul; Liya, Israt Jahan; Basher, Mohammad Anwarul
Abstract: Ethnopharmacological relevance: Fimbristylis miliacea (L.) Vahl ( Cyperaceae ) is a grass like herb usually grows as a weed in rice fields and is mainly distributed in tropical or sub-tropical countries of south and south-east Asia, central America, northern Australia and west Africa. The plant has been traditionally used to treat fever as a form of poultice. Aim of the study: The present study aimed to investigate antipyretic and anti-nociceptive effects of methanol extract of leaves of Fimbristylis miliacea in mice model. Materials and methods: Antipyretic effect of Fimbristylis miliacea was examined using Baker's yeast induced hyperthermia test. Anti-nociceptive effect was investigated using acetic acid induced writhing test, formalin induced hind paw licking test and hot plate test. Results: The extract at concentration of 400 mg/kg produced significant reduction in body temperature after 0.5 h of administration (4.12 °F, p ≤ 0.001) and continued to decrease (after 4 h, 5.92 °F, p ≤ 0.001). Extracts at 100 mg/kg and 200 mg/kg decreased the temperature by about 2.77 °F (from 99.47 °F to 96.7 °F) and 5.58 °F (98.2 °F–92.62 °F) respectively after 4 h whereas paracetamol dropped by about 7.2 °F (p ≤ 0.001). The extract showed significant decrease in number of writhes at all concentrations. Highest effect was found at 200 mg/kg having 35.7 writhes (p ≤ 0.001), much lower than control (89.2); standard drug diclofenac showed 23.2 writhes. Percent inhibition of writhing were 54.26 and 73.99 for 200 mg/kg and diclofenac respectively. The result of hind paw licking test also corroborated writhing test. Significant reduction in percent inhibition of licking was observed mainly in late phase. Percent inhibition of licking were 93.77 and 51.55 for 400 mg/kg extract and diclofenac respectively. In hot plate test, extract at 400 mg/kg showed significant increase in latency from 10.77 s to 13.59 s (p ≤ 0.05). Extract at this dose after 2 h demonstrated greater percent maximal effect (43.26%) compared to ketorolac (40.19%). Conclusion: The experiment confirmed the traditional use of F. miliacea in the treatment of fever with possible anti-nociceptive effects. Graphical abstract: Image 1